Painitng of Samavasarana on the ceiling of the Mandapa - Temples of India Project Team (Jio Institute, 2024)
A painitng of Samavasarana on the ceiling of the mandapa (pillared hall) of the Bhandasar Temple. Samavasarana is a divine preaching hall of the Jains which is designed in the form of four circular passages, each having four entrances. At the centre of the innermost circle sits the Tirthankara followed by other monks of the tradition, laypersons and ascetics. The circle next to this is populated with animals. The outermost circle depicts a procession of elephants. The size of the preaching hall depends upon the enthroned Tirthankara.